2020
DOI: 10.33545/26643766.2020.v3.i3b.154
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and causes of failed spinal anesthesia in a tertiary care Hospital: A retrospective observational study

Abstract: Introduction: Spinal anesthesia (SA) is one of the most frequently applied anesthesia procedures today. However, SA failure rate varies between 1 and 17%. The age of the patient, the position at which the procedure is performed, or the characteristics of the technical operation can affect success. In this study, we aimed to compare the most frequent SA failures according to the types of surgery and causes of failure. The results of SA procedures performed in a Hospital were comparing to those published in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…When SA is used for laparotomy the reasons for conversion from spinal to general anesthesia (GA) are numerous, but it has been reported that, it is failure of spinal anesthesia (48%), followed by prolongation of time of the surgery. Failure of SA can occur by different mechanisms, for example when the subarachnoid space is not reached or the analgesia is not sufficient for surgery after drug injection 26 .…”
Section: Resultsmentioning
confidence: 99%
“…When SA is used for laparotomy the reasons for conversion from spinal to general anesthesia (GA) are numerous, but it has been reported that, it is failure of spinal anesthesia (48%), followed by prolongation of time of the surgery. Failure of SA can occur by different mechanisms, for example when the subarachnoid space is not reached or the analgesia is not sufficient for surgery after drug injection 26 .…”
Section: Resultsmentioning
confidence: 99%